2 - Of Fundamental Change and No Change: Pitfalls of Constitutionalism and Political Transformation in Uganda, 1995-2005 - Asiimwe, Godfrey B. (Africa Development, 2021)
With Uganda’s turbulent and traumatic post-independence political experience, the take-over of the National Resistance Movement (NRM) in 1986 ushered in a tide of unprecedented hope for political transformation and constitutionalism. NRM’s ten-point programme, pledge for a ‘fundamental change’, climaxing in the formulation of a new constitution in 1995, encapsulated the state-social contract and hope for the new order. But ten years later, Uganda’ political landscape and power architecture continued to show that political transformation and constitutionalism were still illusory. This article examines political development in Uganda during the first ten years under the new constitution and time of democratic reforms in Africa. The article shows that these years pointed to political reversals epitomised by the preponderance of abuse of human rights, state failures and loss of hope in the war-ravaged north, patrimonialism, autocratic tendencies, and manipulations which were reminiscent of the old dictatorships. The last straw came with the shocking amendment of the embryonic constitution to remove presidential term limits, which were entrenched as a lynch-pin for a smooth transfer of power. This was followed by the military siege of the High Court that crowned the reality that militarism remained the anchor of power in Uganda’s body politic. The independence of the judiciary and legislature remained illusory, as together with the opposition they remained susceptible to bribery, manipulation, intimidation and repression. With an unpredictable constitutionalism and political terrain, the NRM’s promise of a ‘fundamental change’ degenerated into ‘no change’.